Film tourism impacts: a multi-stakeholder longitudinal approach. Issue 3 (2nd July 2020) - Thelen, Timo; Kim, Sangkyun; Scherer, Elisabeth
ABSTRACT: This study examines multiple local stakeholders' perceptions of film tourism impacts to shed light on the complexities of film tourism planning and development, using a longitudinal exploratory research approach. The Japanese TV series Mare (2015) was chosen as the case study. Qualitative interviews with various local stakeholders were conducted over a 21-month-long period of a film tourism development project in Ishikawa Prefecture, Japan. The study found that this film tourism project was initiated with high expectations. However, due to several incidents, such as the controversial rebuilding of a local highway road for promotional purposes, the audience's mixed reception of the series' storyline, and a sexual harassment scandal involving one of the main actors, the film tourism development did not progress as planned. The study also revealed that consultation which included a diverse range of local stakeholders and long-term planning embedded into a larger regional development strategy were key factors for successful film tourism planning and development. We contribute that an investigation of local stakeholders' consultation, diversity, inclusion and long-term embedding is reflected in perceptions across the pre-, during- and post-production stages. These four complexities provide valuable insights and even explanations for local's dynamic perceptions of film tourism impacts.